PIA-SM: multicast based IPv6 anycast routing protocol. (9th May 2006) - Matsunaga, Satoshi; Ata, Shingo; Kitamura, Hiroshi; Murata, Masayuki
Today, the use of anycast address is quite limited. One of the reasons is that there is no routing protocol providing a global anycasting service. In this paper we design and implement a new anycast routing protocol called PIA-SM (Protocol Independent Anycast – Sparse Mode). We focus on PIM-SM (Protocol Independent Multicast – Sparse Mode), which is one of multicast routing protocols available now, to develop an anycast routing protocol, because anycast and multicast have many similar properties. We modified PIM-SM based on differences between multicast and anycast. We next describe the technical issues to be solved in the implementation of PIA-SM. We also show some experimental results to demonstrate PIA-SM, and verify that PIA-SM enables routers to forward an anycast packet to an appropriate node of multiple candidate nodes.